Reseña sobre: Silencing the Past. Power and the Production of the Past, de Michel-Rolph Trouillot (1995) - Lazzari, Axel (Memoria Americana. Cuadernos de Etnohistoria, 2002)
Reseña sobre el libro escrito por Michel-Rolph Trouillot (1995) titulado Silencing the Past. Power and the Production of the Past. Boston, Beacon Press.